Biology Student Perceptions of Information Literacy Instruction in the Context of an Essential Skills Workshop Series - Amy Jankowski; Yadéeh E Sawyer (Issues in Science and Technology Librarianship, 2019)
The University Libraries at the University of New Mexico reconfigured their established library instruction program for biology as part of a broader grant-funded essential skills workshop series for STEM students. This initiative standardized supplementary instruction through seven in-person and online workshops delivered to students through the Biology Department’s four core undergraduate laboratory courses. Post-workshop feedback data were gathered from students throughout the two-year grant period. The present study analyzes this data set—including 3,797 completed student surveys from both library and non-library workshops over the course of four semesters—with the goal of understanding STEM student perceptions of the value of information literacy skills as compared to the general and disciplinary value of other essential intellectual and practical skills. The findings suggest that undergraduate biology students generally perceive information literacy to be among the most valuable and relevant skills introduced through the workshop series. The results have the potential to inform information literacy instruction practices and collaborative efforts with broader essential skills education programs.